Experimental Study on the Rheology and Cryo-Mechanism of Pile-Frozen Soil Interface - Qiang Gao; Zhi Wen; Zhiwei Zhou; Wei Ma; Anatoli Brouchkov; Rui Shi; Yasheng Li (Geofluids)
The rheological behavior of a pile-frozen soil interface can accelerate pile settlement in pile foundation engineering and deteriorate the bearing capacity of the pile in cold regions. This is the core basis for guiding the design of pile engineering and judging the service life of pile foundations. However, it is unclear how the rheological process is affected by the factors which determine the ad-freeze strength at the pile-frozen soil interface. In this paper, based on a series of Multistage Loading Creep Test (MLCT) for pile-frozen Qinghai-Tibet clay soil interface and microscopic observations of frozen soil, the rheological process and the cryo-mechanism of the interface were analyzed. The results showed that the decrease in soil temperature reduce the interface’s instantaneous deformation value and creep rate, which results from the temperature-dependent rheological behavior of ice. The trend also occurs in the soil with coarser particles and the pile with a rough surface. The presence of massive ice in frozen soil benefits the bearing capacity of the interface at a high temperature of -1°C. However, it can considerably increase the interface’s creep rate due to the influence of the rheological properties of ice at a relatively low temperature of -5°C. Either thick lenticular ice lens or chaotic reticulate cryo-structures in the frozen soil surrounding a pile will enhance the interface’s rheological properties. The interface exhibits the lowest instantaneous deformation value and the slowest creep rate for frozen soil with the massive cryo-structure, which is formed with optimum moisture content. From an engineering viewpoint, the settlement of a pile foundation can be reduced by controlling its instantaneous deformation or restraining its creep rate.